DIRECT AND INDIRECT METHODS OF PROOF. THE LEHMUS-STEINER THEOREM - Mihova, Vesselka; Ninova, Julia (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
We describe and discuss the different methods of proof of a given statement and illustrate by logical models the essence of specific types of proofs, especially of direct and indirect methods of proof. Two direct proofs of Lehmus-Steiner’s theorem are proposed.